Adhesion of hand hygiene by professionals in the emergency care of a university hospital - Oliveira, Adriana Cristina de; De Paula, Adriana Oliveira; Souza, Mariana Almeida de; Silva, Alanna Gomes (Revista de Medicina, 2016)
Objective: to evaluate hand hygiene compliance among healthcare workers. Methodology: cross-sectional study, conducted in an emergency department of a university hospital in Belo Horizonte, between May and August 2013, which evaluated through direct observation, the rate of adherence to hand hygiene by healthcare workers. The observations were based on the five moments for hand hygiene indicated by the World Health Organization. data were analysed using spss software, by descreptive and univariated analysis. Results: 931 opportunities for hand hygiene were registered, 88.9% among nursing technicians, 6.9% among doctors 3.7% for nurses and 0.5%, nursing assistants, giving a globaL rate of adherence among professionals of 19.4%. Handwashing with soap and water was the most frequent metod used by professionals (47%). Conclusion: the rate of adherence to hand hygiene was considered low, which is worrying ahead to the relevance of such action in infection control.